Allelopathic potential of siam weed (Chromolaena odorata L.) extract for enhancing soybean productivity. Issue 1 (November 2021) - Hasanuddin, H; Hafsah, S; Erida, G; Marliah, A; Bahri, H; Zainabun,; Bobihoe, J; Aryani, D S
Abstract: Many tropical invasive species have strong allelopathic effects. Chromolaena odorata is reported to have the best potential to act as bioherbicide against several weeds on crops. This research was conducted in May-September 2019 to evaluate the efficacy of C. odorata extract on soybean plant. This study employed Randomized Block Design (RBD) Factorial with two factors. The first factor was 4 different doses of C. odorata extracts: 0, 8, 16 and 24 tons ha −1 . The second factor was 3 different times of application: 0, 7 and 14 days after planting. Variables observed were number of pods per plant, seed weight per plant, weight of 100 seeds and dry seed yield. The findings indicated that the extract did have effect on seed weight per plant, weight of 100 seeds and yield of dry seeds. The application of extract 16-24 tons ha −1 has improved the seed weight per plant, weight of 100 seeds, and yield of dry seeds. There was no interaction between siam weed extract and time of application in all variables observed.